Potential of Metroxylon sagu Flour as an Alternative Medium for Escherichia coli Growth: A Papuan Carbohydrate Source for Microbiology Laboratory independence - Sarima Sarima; Makmum Ashari; Witri Winanda; Mona Fathia (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2026)
Background: Commercial microbiological media such as Nutrient Agar (NA) are widely used for cultivating non-fastidious bacteria, but their cost and procurement time may limit routine microbiology practicums in eastern Indonesia. This study evaluated Papuan sago (Metroxylon sagu Rottb.) flour as a local alternative medium for Escherichia coli growth.  Methodology: A comparative laboratory experiment was conducted using NA as the control and a sago flour-based medium formulated from 10 g sago flour, 4 g agar, 7 g glucose, and 1 g monosodium glutamate in 500 mL distilled water. E. coli suspensions standardized to 0.5 McFarland were serially diluted, spread-plated in triplicate, and incubated at 37 °C for 48 h. Colony counts were calculated from the 10-4 dilution because all replicate plates were within the countable range. Findings: The sago flour medium supported E. coli growth up to 4.5 × 10⁶ CFU/mL, lower than the 11 × 10⁶ CFU/mL obtained on NA, but still showing consistent growth viability. The relative effectiveness of the sago flour medium reached 40.9% of the standard medium. Colonies on sago medium remained circular, entire, and convex but were smaller and milky white. The reduced growth suggests that sago flour mainly supplies carbohydrates, while nitrogen and mineral availability may remain limiting. Contribution: Papuan sago flour is feasible as a low-cost educational medium for demonstrating bacterial growth, although further enrichment with nitrogen and mineral sources is required before it can approach the performance of NA